Pengembangan Evaluasi Pembelajaran Menggunakan Educaplay Pada Subtema Kewajiban dan Hakku di Rumah: Pengembangan Evaluasi Pembelajaran Menggunakan Educaplay Pada Subtema Kewajiban dan Hakku di Rumah - Lina Novita; Alifya, Diska Putri; Rini Sri Indriani (Department of Education Faculty of Teacher and Training Education University of Jember, 2025)
The purpose of this study is to produce a learning evaluation product using educaplay on the sub-theme of my obligations and rights at home, in class III-A of SDN Ciheuleut 02 with 23 participants. The development of this product uses the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The research begins with need analysis, curriculum analysis, learner analysis, product design, then developing learning evaluation products, validating experts and conducting limited trials of learning evaluation using educaplay on the sub-theme of my obligations and rights at home on predetermined respondents. The validation research result from subject matter experts, language experts and media experts show that learning evaluation using educaplay is highly valid and very suitable for use, obtaining an average percentage of 93,32%. In the trial phase, with 23 participants, respondents responded very well and found it very interesting to use, obtaining an average percentage of 88,52%. Based on the research results, it can be concluded that learning evaluation using educaplay on the sub-theme of my obligations and rights at home developed in this study is proven to be valid, easy and interesting for learners to use and is worthy of being studied. Keywords: Development, Learning Evaluation, Educaplay